Immediate effects of variable durations of pressure release technique on latent myofascial trigger points of the levator scapulae: a double-blinded randomised clinical trial. Issue 3 (June 2019) - Pecos-Martin, Daniel; Ponce-Castro, Manuel José; Jiménez-Rejano, José Jesús; Nunez-Nagy, Susana; Calvo-Lobo, César; Gallego-Izquierdo, Tomás
Objective: Latent myofascial trigger points (MTrPs) of the levator scapulae have a high prevalence and may influenceconditions of the neck and shoulder. The pressure release technique is one of the most recommended manual therapy techniques. The aim of this study was to determine the effect of varying durations of the pressure release technique application on latent MTrPs of the levator scapulae. Methods: In a three-arm (1:1:1 ratio), double-blinded, parallel, randomised clinical trial, 60 healthy university students (23 men, 37 women) with a mean±SD age of 20.0±2.67 years were recruited. Subjects were assigned to receive pressure release in one latent MTrP of the levator scapulae lasting 30s (T30s ; n=17), 60s (T60s ; n=22) or 90s (T90s ; n=21). Active cervical range of movement (CROM), strength, pressure pain threshold (PPT) and neck pain intensity at full stretch were measured immediately before and after treatment. Results: Mixed-model analyses of variance showed statistically significant differences for PPT (P=0.045; partial Eta 2 =0.103), comparing T60s versus T30s (P=0.009; Cohen's d =1.044) and T90s versus T30s groups (P=0.001; Cohen's d =1.253), and for left side bending strength (P=0.043; partial Eta 2 =0.105), comparing T90s versus T30s (P=0.023; Cohen's d =0.907). The rest of the comparisons did not present any significant differences (P⩾0.05). Conclusions: The 60 s and 90 s applications of the pressure release technique may be recommended to increase PPT and strength, respectively, in latent MTrPs of the levator scapulae in the short term. Trial registration number: NCT03006822.